Disagreement aversion - Antoine Bommier; Adrien Fabre; Arnaud Goussebaïle; Daniel Heyen (ETH Zurich, CER-ETH - Center of Economic Research, 2022)
Experts often disagree. A decision-maker may be averse to such expert disagreement. Existing models of aversion to expert disagreement rest on ambiguity-averse preferences adopting a unanimity principle: If all experts consider one choice better than another, so should the decision-maker. Such unanimity among experts, however, can be spurious, masking substantial disagreement on the underlying reasons. We introduce a novel notion of disagreement aversion to distinguish spurious from genuine unanimity and develop a model that can capture disagreement aversion in our sense. The central element of our model is the cautious aggregation of experts' beliefs.
Keywords: D81; D83; D71; 330; Disagreement Aversion; Ambiguity Aversion; Belief Aggregation; Decision under Uncertainty; Precautionary Principle